Community security problems in the state of the Prophet (PBUH)Class disparity in the economic aspect as a model - kazim karim, rusul; Adnan Abdul Wahid , Prof. Dr. Intisar (Thi Qar Arts Journal, 2024)
The research to shed light on one of the societal seurity problems that the islamac commonity in medina suffered from during the era of the messenger of god which is class disparity as many members of society were unable to get rid of the sediments of their ignorant  environment in which they grew up and were raised in thought and dehavior and tai th did not deepen in their hearts thair main problem is the shallowness of their knowledge of monotheism as the society